Status of Carbapenemase Encoding Genes among Imipenem Resistant Acinetobacter baumannii Isolated from Different Samples at a Tertiary Care Hospital in Bangladesh (Bangladesh Journal of Infectious Diseases, 2025)
Background: Nosocomial infections caused by carbapenem-resistant Acinetobacter baumannii are a global health problem.Objectives: The aim of this study was to investigate the molecular mechanisms of carbapenem resistance in Acinetobacter baumannii clinical isolates recovered from a tertiary care hospitals in Bangladesh.Methodology: This cross-sectional study was conducted in the Department of Microbiology of Dhaka Medical College and Hospital, Dhaka, Bangladesh over a period of one year from July 2015 to June 2016. Acinetobacter baumannii was isolated from different specimens and was identified and were screened for carbapenemase production using imipenem discs. Phenotypic identification of carbapenemase production was done by the double disc synergy (DDS) test, combined disc (CD) assay, and modified Hodge test (MHT). The minimum inhibitory concentration (MIC) of imipenem was determined by the agar dilution method. Genes encoding blaNDM-1, blaIMP, blaVIM and blaKPC were identified by polymerase chain reaction (PCR).Results: Twenty-one (80.8%) imipenem resistant Acinetobacter baumannii were detected among 26 isolates. Among 21 imipenem resistant Acinetobacter baumannii, 20(95.2%) carbapenemase producers were detected by PCR, 16(76.2%) by DDS test, 18 (85.7%) by CD assay and 5(23.8%) were detected by MHT. The blaNDM-1 gene was most prevalent 18 (85.7%) followed by blaVIM 14 (66.7%), blaIMP 8(38.1%) and blaKPC 5(23.8%). The minimum inhibitory concentration of imipenem of the imipenem resistant Acinetobacter baumannii ranged from ≥256 μg/ml to 8 μg/ml.Conclusion: This study shows a significant proportion (95.2%) of imipenem resistant Acinetobacter baumannii were carbapenemase producers. Genes encoding carbapenemase enzyme including blaNDM-1, blaVIM, blaIMP and blaKPC are responsible for imipenem resistance.Bangladesh Journal of Infectious Diseases, June 2025;12(1):27-33